STUDENTS' SOCIAL AND PROFESSIONAL MOBILITY AS A PREREQUISITE OF DYNAMIC CAREER PROSPECTS - Evald F. Zeer (Образование и наука)
The paper is devoted to the problems of students' social and professional mobility in the post-industrial society, given the dynamism and uncertainty of future career prospects, and variability and multidimensionality of individual career trajectories.The research is aimed at defining the phenomenon of social and professional mobility, determining factors of professional growth, and functional structural characteristics of mobility development.The scientific novelty involves the author's interpretation and conceptual analysis of students’ socio-professional mobility, and its contribution to the future professional growth. The author considers both the objective and subjective factors affecting the uncertainty of students' professional future: objective factors include socio-economic conditions of postindustrial society, systems of vocational education and guidance; subjective factors deal with the intrapersonal conflicts of professional self-determination, discrepancy of socio-professional orientation, and low auto-competency level.The research findings reveal the structure and characteristic features of students' social and professional mobility: psycho-physiological qualities, cognitive abilities, socio-professional experience and orientation, as well as the negative impact factors. Based on the content analysis and expert evaluation, the author singles out and defines the key characteristics of students’ mobility: adaptability, initiative, innovativeness, learning ability, behavioral flexibility, reflexivity and excessive activity.Practical significance: the research outcomes provide the ground for extrapolation of students' career prospects in vocational schools, career counseling and job placement centers.